HajraMasroor: An Icon of Feminist Literature in Pakistan - Dr. Mamataz Kalyani; Ishrat Hussain (Zaban-o-Adab, 2021)
Urdu literature is becoming riches by women writings. This paper seeks to offer a reading of HajraMasroor short stories in feminist perspective. In Masroor’s formative years, IsmatChughtai, Dr. Rashid Jahan and Qurrat-ul-AinHaider had established herself an independent a feminist voice. HajraMasroor wrote extensively on themes including female sexuality and femininity, middle class gentility political and economical rights for women. With a style characterized by literary realism, She established herself as a significant voice in the Urdu literature. In October 1947, HajraMasroor’sfamilty migrated to Pakistan, Masroor and Ahmed NadeemQasmico edited the prominent Urdu literary magazine Naqoosh. In Pakistan she wrote on the condition and role of women in this country. She was very passionate about bringing social change in society, she zealously wrote about social equality of women in Pakistan. Indeed, she had shown her appearance in the Urdu literature and fiction with bold imagination. She works short stories in non-traditional way. The methodology focused on the textual analysis to reveal the feminist concept of her. She spoke of sexuality, abortion lesbianism and desires of women.